Occurrence of the radionuclides in groundwater of crystalline hard rock regions of central Tamil Nadu, India - Thivya, C.; Chidambaram, S.; Tirumalesh, K.; Prasanna, Mohan Viswanathan; Thilagavathi, R.; Nepolian, M. (Springer, 2014)
A study was conducted to understand the occurrence of the radionuclides in groundwater of crystalline hard rock region. Samples were collected to analyze major cations, anions, U, 222 Rn and stable isotopes of oxygen, hydrogen. It was inferred that few samples have U and 222 Rn concentrations higher than the permissible limit of drinking water standard. High degree of weathering of granitic rocks and long contact time of groundwater with the aquifer matrix could be the reason for enhanced U and 222 Rn levels in groundwater. The association of U with SO4 also proves that there exists anthropogenic influence in groundwater composition.